Sodium New Houttuyfonate Affects Transcriptome and Virulence Factors of Pseudomonas aeruginosa Controlled by Quorum Sensing - Zhao, Yeye; Mei, Longfei; Si, Yuanqing; Wu, Jiadi; Shao, Jing; Wang, Tianming; Yan, Guiming; Wang, Changzhong; Wu, Daqiang (Frontiers in Pharmacology, 2020)
As a major opportunistic pathogen, Pseudomonas aeruginosa can produce various virulence factors and form biofilms. These processes are controlled by the quorum sensing (QS) system. Sodium new houttuyfonate (SNH) is an adduct of houttuyfonate, the main component of the common Chinese medicine plant Houttuynia cordata, which has antibacterial and anti-inflammatory effects. We evaluated the effect of SNH on P. aeruginosa biofilms, virulence factors, and transcription. Transcriptome analysis showed that the key rhlI and pqsA genes of the P. aeruginosa QS system was down-regulated after SNH treatment. SNH reduces proteases and pyocyanin production and inhibits biofilm formation by regulating the P. aeruginosa QS system. SNH also changes the expression of genes related to virulence factors and biofilms (lasA, lasB, lecA, phzM, pqsA, and pilG). These results provide further evidence that the mechanism of SNH against P. aeruginosa involves biofilm and virulence factors.